Perfection of hoe-type motions of sportswomen specialized in synchronous swimming in base positions of compulsory exercise - Gordieieva, M. V. (Physical Education of Students, 2013)
The features of implementation of standard hoe-type motion of sportswomen of the synchronous swimming are certain. In an experiment took part 16 sportswomen aged 8-11 years. Distinctions are exposed between the index of resulting speed of centre-of-mass biotlinks of overhead extremities of sportswomen and between kinematics and dynamic descriptions at implementation of a few types of standard hoe-type motion. It is recommended at the end of every mesocycle to conduct current control with the use of videosurvey. To conduct the analysis of video data and discussion of suffered sportswomen technical errors. It is suggested to draw on the complex of tricking into and imitation exercises, exercises on development of force and flexibility in joints, exercises on perfection of rhythm structure of motive action. It is recommended to execute motive actions on a background of considerable physical fatigue, emotional overvoltage, distraction, up-diffused attention, difficulty of activity of separate analyzers (motive actions with the closed eyes).